Wireless sensor network for fire detection with network coding to improve security and reliability - Johannes Braun; Faouzi Derbel (Measurement: Sensors)
This article proposes a wireless sensor network (WSN) for fire alarm systems that leverages network coding to enhance system reliability and security. The proposed WSN is designed to comply with European standards, with a particular focus on German standards, and enables the deployment of sensor nodes that automatically construct a robust and reliable network. The self-healing, redundant, decentralized routed network ensures uninterrupted functionality in case of a communication failure. The network coding technique is utilized to manage the surge in data traffic during hazard situations, reducing the overall number of telegrams while maintaining data integrity and reliability. By implementing network coding, the proposed WSN reduces energy consumption and enhances the efficiency and reliability of fire alarm systems, thereby contributing to greater safety in emergency situations. To further leverage the advantages of network coding, a new decentralized routing technique is introduced. This technique operates locally on nodes through the use of virtual cluster heads and an innovative Weighted Composite Value (WCV) Table, optimizing routing decisions for improved performance and scalability. This article provides a comprehensive exploration of the benefits of network coding in WSNs for fire alarm systems and presents a real-world implementation, demonstrating its potential for improving the performance of these systems.